2012
DOI: 10.1111/imig.12024
|View full text |Cite
|
Sign up to set email alerts
|

Salvadoran Migrants in Australia: An Analysis of Transnational Families’ Capability to Care across Borders

Abstract: In this paper, I focus on the transnational care practices of Salvadoran refugees living in Perth (Western Australia) and who care for their ageing parents who have remained in their home country. The analysis is based on a conceptualization of transnational care as a set of capabilities that include, but are not limited to, mobility, social relations, time allocation, education and knowledge, paid work and communication (Merla and Baldassar, 2011). I focus in particular on the impact of Salvadoran refugees’ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 12 publications
3
37
0
2
Order By: Relevance
“…This reflects the findings of scholars who have looked at gender and skilled migration in various contexts (see for example , Ho 2006;Ryan 2007;Raghuram 2004). Skilled migration can be associated with downward social mobility and economic instability (Datta et al 2009;Merla 2012). This is particularly pronounced for women, resulting in under-employment, a shift away from the chosen career or retraining, and can add additional pressure to childcare responsibilities (Meares 2010).…”
Section: Westcott and Robertson: Childcaresupporting
confidence: 63%
“…This reflects the findings of scholars who have looked at gender and skilled migration in various contexts (see for example , Ho 2006;Ryan 2007;Raghuram 2004). Skilled migration can be associated with downward social mobility and economic instability (Datta et al 2009;Merla 2012). This is particularly pronounced for women, resulting in under-employment, a shift away from the chosen career or retraining, and can add additional pressure to childcare responsibilities (Meares 2010).…”
Section: Westcott and Robertson: Childcaresupporting
confidence: 63%
“…At a macro-level, we have built on our own work (Merla and Baldassar, 2011;Merla, 2015) and its further elaboration with Majella Kilkey (Kilkey and Merla, 2014; see also Merla, 2014a) to show how institutional contexts shape the 'capability' (Robeyns, 2003) of transnational family members to circulate care across borders. The specific position that individuals occupy within the migration, welfare, gendered care and social employment regimes of their home and host countries plays a key role in facilitating or hindering their access to the temporal, material, and social resources that are needed to engage in transnational care practices.…”
Section: Bringing Back the 'Political'mentioning
confidence: 99%
“…Ryan et al (2009) suggested that while Polish migrants in London were not able to provide physical care, they sent financial remittances back home to support aged and child care. They and Merla (2015) also noted that migrants and their left-behind families provided mutual emotional support through various communication mechanisms.…”
Section: Transnational Family Practicesmentioning
confidence: 99%
“…Bonizzoni (2015) found that left-behind adult children of migrants are more actively involved in transnational familial linkages than non-adult children. Merla (2015) found that labour market conditions in destination countries, restrictive visa regulations, and inadequate access to community facilities restricted the strength of transnational familial linkages. At the macro level, studies have suggested that transnational family linkages are strengthened by more affordable travel and communication technologies (Baldassar, 2007;Carling, Menjivar, & Schmalzbauer, 2012), policies on eliminating barriers to reunification in countries of origin and destination (Zentgraf & Chinchilla, 2012), and public interventions such as funding and social services to spatially separated families (Baldassar, 2007;Zentgraf & Chinchilla, 2012).…”
Section: Transnational Family Practicesmentioning
confidence: 99%